On stethoscopes, patient records, artificial intelligence and zettabytes: A glimpse into the future of digital medicine in mexico Sobre estetoscopios, expedientes clínicos, inteligencia artificial y zettabytes: Una mirada al futuro de la medicina digital en méxico - Araiza-Garaygordobil D.; Jordán-Ríos A.; Sierra-Fernández C.; Juárez-Orozco L.E. (Instituto Nacional de Cardiologia Ignazio Chavez, 2022)
Science and technology are modifying medicine at a dizzying pace. Although access in our country to the benefits of innovations in the area of devices, data storage and artificial intelligence is still very restricted, the advance of digital medicine offers the opportunity to solve some of the biggest problems faced by medical practice and public health in Mexico. The potential areas where digital medicine can be disruptive are: accessibility to quality medical care, centralization of specialties in large cities, dehumanization of medical treatment, lack of resources to access evidence-supported treatments, among others. This review presents some of the advances that are guiding the new revolution in medicine, discusses the potential and potential barriers to implementation, and suggests crucial elements for the path of incorporation of digital medicine in Mexico.